Redescription of Hisonotus notatus Eigenmann & Eigenmann, 1889 (Loricariidae: Hypoptopomatinae), The type species of the genus, and description of a new species from coastal drainages of southeastern Brazil - Martins, Fernanda O. [UNESP]; Langeani, Francisco [UNESP] (FapUNIFESP (SciELO), 2016)
Our analyses showed that the type series of Hisonotus notatus, type species of the genus, is mixed, composed by two different species. Based on that, we redescribe H. notatus with the designation of a lectotype, restricting the species to rio São João drainage and other small coastal drainages running to the Baía de Guanabara and to the Baía de Sepetiba in Rio de Janeiro State. We also describe a new species of Hisonotus from drainages of the rio Paraíba do Sul, Lagoa Feia, rio Macaé, and coastal rivers of Espírito Santo State, from rio Itabapoana to rio Doce basin. These two species are sister-taxa and can be distinguished by the number of plates in the mid-dorsal series.
Keywords: Biodiversity; Cascudinhos; Lectotype; Siluriformes; Taxonomy